The role of innate immunity and angiogenesis in osteosarcoma growth and metastasis - Sottnik, Joseph L., author; Dow, Steven W., advisor; Thamm, Douglas, advisor; Weil, Michael M., committee member; Biller, Barbara J., committee member (Colorado State University. Libraries, 2010)
Osteosarcoma is the most common primary bone tumor in dogs and humans. Novel therapeutics are required since a number of patients will succumb to metastatic disease. Currently, it is known that a neoplastic mass contains more than transformed cells, but requires the presence of immune cells to create a supportive environment, and endothelial cells to form blood vessels to deliver oxygen and nutrients. Not only do these cells play a role in primary tumor growth, but they create an atmosphere conducive to invasion and metastasis, the primary cause of death for osteosarcoma patients. Therefore, better understanding of how immune and endothelial cells support metastatic growth is crucial for better understanding osteosarcoama. Utilizing murine tumor models, we have been able to explore the observation that patients with post-surgical infections have increased time to metastasis and increased survival. We have determined that this effect is mediated by NK cells and monocytes, which inhibit tumor growth through restriction of angiogenesis. We have also investigated the role of an anti-inflammatory therapeutic, tepoxalin, which leads to tumor growth inhibition. These observations explain the paradox of inflammation, where the type and timing of inflammation may inhibit or promote an anti-tumor effect. Due to the importance of angiogenesis and metastasis in osteosarcoma, we sought to develop new models and techniques to assess these processes. Fine needle aspiration coupled with flow cytometry accurately measures angiogenesis in cutaneous tumors, thereby allowing for repeated assessment of angiogenesis in a minimally invasive manner. We have also developed a novel post-surgical model of luciferase transfected murine osteosarcoma that grows orthotopically and spontaneously metastasizes, allowing us to non-invasively investigate the development of metastases. These tools will allow for investigation into novel anti-angiogenic and anti-metastatic compounds. Novel prognostic markers are required to better determine the outcome of cancer patients. We have determined that monocyte and lymphocyte counts from a pre-treatment complete blood count are prognostic for disease free interval in dogs with osteosarcoma. These data describe the interactions between immune infiltrate and metastasis. The combination of the studies presented herein provides evidence for the interactions between the immune system and angiogenesis in the process of metastasis.
Department Head: Paul J. Laybourn.
Keywords: metastasis; osteosarcoma; murine models; Osteosarcoma; Neovascularization; Bone metastasis